La relance des bacheliers en criminologie de 1970 à 1983 - Dionne, Michèle (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
What is the situation on the labour market today for graduates of the School of Criminology who obtained their bachelor degrees from 1970 on? Based on the answers to a questionnaire covering the 14 years concerned, the professional careers of 546 of the 1001 graduates are traced and described. Of these, 48% are men and 52% women, 48% being between the ages of 25 and 30. The survey shows that two out of three graduates have jobs directly related to their training, that their principal employer is the civil service and that there is less room in the workplace for women than for men.